Immune response to flour and dust mites in a United Kingdom bakery. Issue 8 (August 1992) - Tee, R D; Gordon, D J; Gordon, S; Crook, B; Nunn, A J; Musk, A W; Venables, K M; Taylor, A J
Abstract : In a study of 279 United Kingdom bakery workers a high prevalence of immunological response to storage mites was found. To determine whether this was the consequence of exposure to storage mites in bakery work, a population of salt packing workers was examined as a comparison group not at occupational risk of exposure to storage mites. Forty two per cent of both groups were atopic (had a positive skin prick response greater than negative controls to D pteronyssinus, grass pollen, or cat fur by 2 mm or more) and 33% had an immediate skin prick test response to at least one of four storage mites (L destructor, G domesticus, T putrescentiae, A Siro). A higher percentage of the salt packing workers than the bakery workers had a positive radioallergosorbent test (RAST) (greater than or equal to 0.35 PRU) to D pteronyssinus and to the four storage mites. Logistic regression analysis identified atopy as the most significant variable for a positive skin test and RAST response to storage mites in both groups of workers. RAST inhibition was used to analyse extracted area and personal air samples. Analysis of static area samples for aeroallergen showed immunological identity with flour but L destructor was found in only one of seven exposed filters. The concentration of airborne flour was related to exposure rank of perceived dustiness and gravimetric measurement of total dust. Nineteen out of 32 filters from workers in jobs with higher dust exposure (rank >/=6) had a level of > 10 microgram/m(3) flour whereas this concentrations was exceeded in only one of 23 filters from workers in low dust exposure (< rank 6). It is concluded that storage mites are not of special significance in allergic responses in bakery workers. The development of immunological (and airway) responsiveness to inhaled flour dust is increased in those exposed to higher concentrations of airborne allergen, which appears to be predominantly flour and not storage mites.